Boas práticas na comunicação audiovisual em startups, relacionando o caso do estudo da startup door2Door com o contexto do UPTEC - Simão Manuel Lopes Pereira (2017)
This study pretends to start correlating two startup ecosystems, in Porto and Berlin, culminating in a series of guidelines regarding communication strategies. Identifying social and cultural phenomena relevant in the fields of media and audiovisual art, as well as nowadays panorama in terms of visual communication, by research and interviews with key figures in the area. This guidelines will then be of use for startups in early stages, as well for young entrepreneurs in Porto.